FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN PRE OPERASI DI IBS RSUD TAMAN HUSADA BONTANG - Santosa; Rasmun; Frana Andrianur (Jurnal Cakrawala Ilmiah, 2024)
Background: Excessive preoperative anxiety can cause a pathological response so that the body will produce excessive cortisol hormone which will result in increased blood pressure, tachycardia, arrhythmia, chest tightness and severe pain which can persist until the post-operative period. One of the consequences of excessive anxiety is an increase in blood pressure, in this situation if the operation continues there will be a risk of causing bleeding and difficulty in stopping the bleeding, even after surgery it will disrupt the healing process Objective: To determine the faktors related to the preoperative anxiety level of patients at IBS, Bontang Regional Hospital Method: This research is a type of quantitative research with a cross sectional study approach of preoperative patient anxiety levels at Bontang Regional Hospital. The population in this study was all pre-operative patients at the Bontang District Hospital during the period July – August 2023, estimated + 100 people. The sampling technique in this study was carried out using the total sampling method. Covers pre-operative patients at IBS, Taman Husada Bontang Regional Hospital during the period July – August 2023, estimated at + 100 people. Results: Based on the results of bivariate analysis, it was found that there was a relationship between the faktors age, gender, education, occupation and knowledge on preoperative patient anxiety in the IBS room at Taman Husada Hospital, Bontang with a P value <0.05 Conclusion: there is a relationship between the faktors age, gender, education, occupation and knowledge on preoperative patient anxiety in the IBS room at Taman Husada Hospital, Bontang